2021
DOI: 10.1186/s12882-021-02568-8
|View full text |Cite
|
Sign up to set email alerts
|

Remnant renal volume can predict prognosis of remnant renal function in kidney transplantation donors: a prospective observational study

Abstract: Background Safety and survival during and after donor nephrectomy (DN) are one of the main concerns in living kidney donors (LKDs). Therefore, kidney (left/right) to be procured should be determined after considering the difficulty of DN, as well as the preservation of remnant renal function (RRF). In this prospective study, we investigated the roles of computed tomography volumetry (CTV) in split renal function (SRF) and established a predictive model for RRF in LKDs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
(29 reference statements)
1
4
1
Order By: Relevance
“…The influence of cortex volume on postdonation renal function has been addressed previously, demonstrating correlations between volume and GFR after 1 y. 30,[34][35][36] Our data further reveal that cortex volume is independently associated with renal outcome even after adjustment of multiple factors including GFR of the nondonated kidney. Recent reports suggest that contrast-enhanced CT scans with determination of cortex volume could substitute measurement of skGFR.…”
Section: Renal Outcome In Lkdssupporting
confidence: 72%
“…The influence of cortex volume on postdonation renal function has been addressed previously, demonstrating correlations between volume and GFR after 1 y. 30,[34][35][36] Our data further reveal that cortex volume is independently associated with renal outcome even after adjustment of multiple factors including GFR of the nondonated kidney. Recent reports suggest that contrast-enhanced CT scans with determination of cortex volume could substitute measurement of skGFR.…”
Section: Renal Outcome In Lkdssupporting
confidence: 72%
“…The association with (cortical) kidney volume is in line with previous studies connecting kidney volume with (post-donation) GFR. 8,32 Our findings pave the way for future studies that identify underlying molecular mechanisms, define biomarkers and reveal the clinical potential of the post-donation increase in single-kidney GFR, both in and beyond kidney donation.…”
Section: Discussionmentioning
confidence: 82%
“…Mean eGFR was 91±15 mL/min/1.73m 2 before donation, 59±13 mL/min/1.73m 2 at three months post-donation (P<0.001 vs. pre-donation), and 62±13 and 63±13 mL/min/1.73m 2 at five and ten years after donation (both P<0.001 vs. three months post-donation). Median [25 th -75 th percentile] increase in eGFR beyond 50% of the pre-donation eGFR at three months post-donation was 12 [8][9][10][11][12][13][14][15][16][17][18] mL/min/1.73m 2 .…”
Section: Characteristics Of the Donor Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, significant advances have been made in the application of deep learning-based computer vision in urology. The medical imaging software used in the present study has previously shown success in reconstructing 3D simulations of kidney-specific anatomy from CT/MRI, which has since helped facilitate clampless PN and predict residual renal function in kidney transplant settings 14 , 27 . The same software also led to more accurate estimations of NBGFR after RN in RCC patients when compared to subjective estimations of NBGFR made by expert urologic oncologists 6 .…”
Section: Discussionmentioning
confidence: 99%